Factors that influencing purchase intention towards counterfeit fashion / Nur Irdina Syazwani Abu Bakar - Abu Bakar, Nur Irdina Syazwani (Faculty of Business and Management, 2019)
The study aims to identify which factors that strongly influences consumer behavior to purchase intention towards counterfeit fashion product. The study is also set out to examine the relationship between factors that influencing customer and purchase intention towards counterfeit fashion product. A theoretical framework is proposed by following the studies of Bhatia, V. (2018). The factor that is believed to influence the purchase intention of customer in the study of Bhatia (2018) are social influence, materialism, value consciousness, perceived risk and brand consciousness. A survey of 180 respondents was conducted in Bandaraya Melaka by using convenience sampling and the data is analysed by using SPSS 20 to get a clear result. Pearson correlation, multiple regression and Cronbach Alpha test were used to test the suggested hypotheses and research question. The result indicated that social influence, value consciousness and brand consciousness have positive relationship with purchase intention while perceived risk have negative relationship with purchase intention which are following the path of this research study. The result also shows that perceived risk has the strongest impact on purchase intention, Based on this results, several recommendations have been made for fashion retail companies and also for future research purposes.